Study the effect of Enterobacter cloacae on the gene expression, productivity, and quality traits of Curcuma longa L. Plant - Alrajeh, Hind Salih; Sherif, Fadia El (Frontiers in Plant Science, 2024)
Overuse of artificial chemical fertilizers could be detrimental to the environment. Utilizing beneficial microorganisms as biofertilizers is a sustainable technique that promotes soil health, crop yield, and ecosystem preservation. Curcuma longa L. is utilized as a medication since it has its antibacterial, anti-microbial, and anti-tumor characteristics, which reduce inflammation and hasten wound healing. The effect of E. cloacae strain MSR1, which is common in the roots of alfalfa grown in the Al-Ahsaa region, on C. longa plants is being investigated. C. longa rhizomes were planted under greenhouse conditions after being submerged in a solution of E. cloacae strain MSR1 (OD 500) or water treatment as a control for 12 hours. After 240 days of growing, ten randomly selected plants from each treatment were collected, and the vegetative growth and yield metrics were assessed. To investigate how E. cloacae influences C. longa production and chemical composition (photosynthetic pigment, nitrogen, phosphorus, potassium, and curcuminoid), measurements were conducted as well as genes diketide-CoA and curcumin synthases genes. Our research showed that C. longa's growth and yield were favorably impacted by E. cloacae. Significant increases in the related plants' chlorophyll a,b, carotenoid, nitrogen, phosphorus, and potassium levels were likewise a reflection of the enhanced effects shown in the growth and yield parameters. Treatment with E. cloacae raised the curcuminoid's three sub-components' compositions to varying degrees: bisdemethoxycurcumin, demethoxycurcumin, and curcumin. Comparing E. cloacae treated plants to the control, high expression levels of the genes diketide-CoA and curcumin synthase-1, -2, and 3 were also found. The treatment of E. cloacae is a good biostimulant candidate for boosting growth and yield as well as raising the medicinal qualities of C. longa, according to the overall results.